2014
DOI: 10.1534/genetics.114.169409
|View full text |Cite
|
Sign up to set email alerts
|

Competence for Chemical Reprogramming of Sexual Fate Correlates with an Intersexual Molecular Signature inCaenorhabditis elegans

Abstract: In multicellular organisms, genetic programs guide cells to adopt cell fates as tissues are formed during development, maintained in adults, and repaired after injury. Here we explore how a small molecule in the environment can switch a genetic program from one fate to another. Wild-type Caenorhabditis elegans XX adult hermaphrodites make oocytes continuously, but certain mutant XX adults make sperm instead in an otherwise hermaphrodite soma. Thus, puf-8; lip-1 XX adults make only sperm, but they can be switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…Therefore, regulation of MPK-1 activity by PUF-8 and FBF-1 reviewed above contributes to germline sex determination. Hyperactivation of MPK-1 and excessive spermatogenesis were observed in puf-8; lip-1 as well as in fbf-1; lip-1 genetic backgrounds (Morgan et al, 2010;Sorokin et al, 2014). In these genetic backgrounds, spermatogenesis was dependent on MPK-1 activity and repressed by a small molecule MEK inhibitor U0126 (Morgan et al, 2010;Sorokin et al, 2014).…”
Section: Puf Function In Controlling the Sperm/oocyte Decision In Germentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, regulation of MPK-1 activity by PUF-8 and FBF-1 reviewed above contributes to germline sex determination. Hyperactivation of MPK-1 and excessive spermatogenesis were observed in puf-8; lip-1 as well as in fbf-1; lip-1 genetic backgrounds (Morgan et al, 2010;Sorokin et al, 2014). In these genetic backgrounds, spermatogenesis was dependent on MPK-1 activity and repressed by a small molecule MEK inhibitor U0126 (Morgan et al, 2010;Sorokin et al, 2014).…”
Section: Puf Function In Controlling the Sperm/oocyte Decision In Germentioning
confidence: 99%
“…Hyperactivation of MPK-1 and excessive spermatogenesis were observed in puf-8; lip-1 as well as in fbf-1; lip-1 genetic backgrounds (Morgan et al, 2010;Sorokin et al, 2014). In these genetic backgrounds, spermatogenesis was dependent on MPK-1 activity and repressed by a small molecule MEK inhibitor U0126 (Morgan et al, 2010;Sorokin et al, 2014). Activation of MPK-1 in fbf-1; lip-1 genetic background likely results from the loss of FBF-mediated repression of mpk-1 translation and the loss of LIP-1-mediated post-translational inhibition of MPK-1 (Lee et al, 2007a).…”
Section: Puf Function In Controlling the Sperm/oocyte Decision In Germentioning
confidence: 99%
“…Interestingly, we found that the Glp phenotype of fbf-1 fbf-2 mutants was sufficiently suppressed by additional removal of PUF-8 (another PUF protein) (Fig. 5A and 5B), a key regulator for C. elegans germline development (Subramaniam and Seydoux, 2003; Ariz et al, 2009; Cha et al, 2012; Racher and Hansen, 2012; Pushpa et al, 2013; Vaid et al, 2013; Datla et al, 2014; Sorokin et al, 2014; Priti and Subramaniam, 2015). The puf-8 fbf-1 fbf-2 triple mutants displayed mitotically dividing cells in the germline (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The sperm and egg in the same flower are fertilized to form new embryos. A similar form of reproduction is seen in hermaphrodite nematodes, called C. elegans [29][30][31][32]. There are also case reports of the co-presence of both the gonad and testis tissues in humans [33].…”
Section: Is the Virgin Mary's Pregnancy With Jesus A Case Of Parthenomentioning
confidence: 99%